Implementasi Metode Vector Space Modelling Untuk Pencarian Buku Pada Perpustakaan - Hartono, Rudi; Siswanto; Kanedi , Indra (CV. Generasi Insan Rafflesia, 2023)
Search Engine is a system that can be used to automatically find relevant information to the needs of its users from a book collection. This system will receive input in the form of keywords for the information to be searched. In a relatively shorter time, it will provide relevant information for the keywords entered by the user. In the search system, one method is needed, one of which is VSM (Vector Space Modeling) method. VSM method was chosen because the way this model works is efficient, easy to represent, and can be implemented in library systems. The system implementation uses the Visual Basic 2010 programming language and the method used in this research is the System Development Life Cycle (SDLC). This SDLC functions to describe the main stages and steps of each stage which are broadly divided into 3 (three) activities, namely analysis, design and implementation. By developing a library system using the VSM method, it is hoped that it will make it easier for officers to provide services and can help with work in the library through library automation functions, so that the library management process is more effective and efficient.